The effect of ethical commitment reminder and reciprocity in the workplace on misreporting - Ferdiansah, Muhammad Irdam (Journal of business ethics, 2023)
Despite the pervasive use of ethics training by companies, research in management accounting has not considered the effectiveness of such training in curtailing managers' misreporting. This study examines the effect of ethics training on misreporting as a reminder to raise the awareness of employees' ethical commitment. Furthermore, this study investigates the extent to which reciprocity in the workplace affects managers' misreporting. The results from an experiment involving 124 managers show that in the absence of an ethical commitment reminder, managers are more likely to engage in misreporting than when an ethical commitment reminder is present. The results suggest that ethical commitment reminder interacts with reciprocity in the workplace, affecting managers' misreporting. Specifically, the results reveal that managers are more likely to engage in misreporting under the reciprocity in the workplace condition when the ethical commitment reminder is absent. The theoretical and practical implications of these findings are discussed.